New Face of Local Government: Synergy of Handling the Spread of Covid-19 Between Local Governments and Indigenous Villages in Bali - I Putu Dharmanu Yudartha (Indonesian Association for Public Administration (IAPA), 2020)
Province Bali province seeks to build synergy in addressing the spread of covid-19 with the involvement of indigenous villages. This is certainly a big question about its effectiveness and provides a new perspective in government governance at the local level. The purpose of this research is to analyze the dimensions of synergy between local governments and indigenous villages in Bali Province and their impact on the handling of covid-19 in Bali. The results showed that the cultural and social dimensions were able to position the indigenous village into an important pillar in the pattern of governance in Bali. Through the policy of the scope of indigenous villages (such as awig-awig and perarem) and pecalang as a security party in the scope of indigenous villages are able to synergize with local governments, especially in overseeing the implementation of health protocols. The synergistic with good local governance concept, such as : dimension of the economic aspect shows that through indigenous village funds, the local government provides the same space for indigenous villages involved in the handling of covid-19. The political dimension related to synergy is further strengthening the commitment of the Governor of Bali to reposition the indigenous village as part of governance in Bali. The synergistic impact is to provide great space for various parties, especially indigenous villages in the participation of each policy in the region. This synergy also relieves the free local government in its handling of covid-19.